Diet analysis of three rodent species sigmodontine in three cocoa production systems and forest in Alto Beni, Bolivia - Calizaya-Mena, Wendy; Rico-Cernohorska, Adriana; García-Estigarribia, Emilia; Valenzuela-Celis, Esther (THERYA, 2020)
Alto Beni region in Bolivia, presents a mosaic of non-extensive family crops ranging from monocultures to agroforestry systems immersed in a matrix of secondary forest, while the primary forest remains on the steeper slopes. Very little is known about the biology of the rodent species that inhabit this area. Then, the objective of this work was to determine the diet and its variation among three species of sigmodontine rodents (Akodon dayi, Euryoryomys nitidus and Oligoryzomys microtis) from 11 agroforestry systems (SAF) of cacao (four traditional monoculture / simple SAF plots, three intermediate SAF and four complex SAF) and two secondary forests. We analyzed contents of the stomach, cecum and intestine for 41 O. microtis (simple-SAF n = 31, complex-SAF n = 4 and forest n = 6), for 11 E. nitidus (simple-SAF n = 6, intermediate-SAF n = 2, complex-SAF n =3 and forest n = 2) and for 10 A. dayi (simple-SAF n =5 and forest n =5). We calculated trophic niche width (Levinâ€™s Index) and measured the degree of niche overlap (an estimate of competition), using Piankaâ€™s Symmetric Overlaying Index. Significant differences in the diet specialization among species across habitats, were tested using the non-parametric Kruskal-Wallis test. A total of 55 food items were obtained and grouped into nine food categories: dicotyledonous vegetative structures, monocotyledonous vegetative structures, vascular tissue, spikelet, seeds, mycorrhizae, adult arthropods, larval arthropods, and others. The study species feed primarily on plants of the family Poaceae. No significant differences were found in the diet between species or between SAF and the forest (P > 0.05); in addition, there was no evidence of a noticeable overlay of trophic niches by habit type. In the studied season, we found that: O. microtis and E. nitidus are herbivorous omnivore; â€œgeneralistâ€ simple-monoculture-SAF and â€œless generalistâ€ in complex-SAF; besides, O. microtis is â€œgeneralistâ€ in forest and E. nitidus is â€œspecialistâ€ in complex-SAF and in forest; while, A. dayi is herbivore-insectivore; â€œgeneralistâ€ in simple-monoculture-SAF and in forest. Our results indicate that there is a strong relationship between, the type of plot where they were found and food availability in each habitat.